Mecanum 4 Omni Wheel Directional Robot Design System Using PID Method - Alfiyan, Muhammad; Puriyanto, Riky Dwi (Journal of Fuzzy Systems and Control, 2023)
Robot or Artificial Intelligence (AI) can be interpreted as a machine with some computer intelligence and controlled by a computer, and has physical abilities like humans. One of the drives of robots that is often used is a DC motor, a DC motor is a motor with an electronic device that converts electrical energy into kinetic energy or motion. However, DC motors often experience a decrease due to the existing load, so that the speed becomes not constant, so it is necessary to design a controller. The controller used is Proportional Integral Derivative (PID). In the PID there are several parameters such as , , and which are selected or determined so that the plant characteristics match the desired criteria. The general parameters are rise-time, settling-time, maximum, overshoot, and steady-state error for a given input. From the results of the DC motor speed control test using the PID method which was carried out by trial and error testing of the four DC motors, the best PID value was obtained with ; ; ; and with the Rise Time system message: 14.7452; Overshoots: 0.6667; Settling Time: 52.0100; Undershot: 0; Settling Min: 136; Peaks: 151; Settling Max : 151; and Peak Time: 65.